Depressed basal hypothalamic neuronal activity in type-1 diabetic mice is correlated with proinflammatory secretion of HMBG1. (26th February 2016) - Thinschmidt, Jeffrey S.; Colon-Perez, Luis M.; Febo, Marcelo; Caballero, Sergio; King, Michael A.; White, Fletcher A.; Grant, Maria B.
Highlights: Hypothalamic neuronal activity is reduced following 8 months of type-1 diabetes in mice. Basal neuronal activity is reduced in the paraventricular nucleus (PVN) following 8 months of type-1 diabetes in mice. Nuclear localization of HMBG1 is reduced in the paraventricular nucleus (PVN) of the hypothalamus following 8 months of type-1 diabetes in mice. Reduced nuclear localization of HMBG1 is correlated with a reduction in basal neuronal activity in the hypothalamus following 8 months of type-1 diabetes in mice. Abstract: We recently found indicators of hypothalamic inflammation and neurodegeneration linked to the loss of neuroprotective factors including insulin-like growth factor (IGF-1) and IGF binding protein-2 (IGFBP-3) in mice made diabetic using streptozotocin (STZ). In the current work, a genetic model of type-1 diabetes (Ins2 Akita mouse) was used to evaluate changes in neuronal activity and concomitant changes in the proinflammatory mediator high-mobility group box-1 (HMBG1). We found basal hypothalamic neuronal activity as indicated by manganese-enhanced magnetic resonance imaging (MEMRI) was significantly decreased in 8 months old, but not 2 months old Ins2 Akita diabetic mice compared to controls. In tissue from the same animals we evaluated the expression of HMBG1 using immunohistochemistry and confocal microscopy. We found decreased HMBG1 nuclear localization in the paraventricular nucleus of the hypothalamus (PVN) in 8 months old, but not 2 months old diabetic animals indicating nuclear release of the protein consistent with an inflammatory state. Adjacent thalamic regions showed little change in HMBG1 nuclear localization and neuronal activity as a result of diabetes. This work extends our previous findings demonstrating changes consistent with hypothalamic neuroinflammation in STZ treated animals, and shows active inflammatory processes are correlated with changes in basal hypothalamic neuronal activity in Ins2 Akita mice.